Cyclization Modes in Anilides of N-Protected 3-Oxo-4-phenylaminobutyric Acid Under Knorr Conditions - Plamen Angelov; Yordanka Mollova-Sapundzhieva (Molbank)
Anilides of 3-oxo-4-phenylaminobutyric acid with Troc or COOEt protection at the phenylamino group undergo competing cyclization processes in neat polyphosphoric acid at 80 °C. Depending on the protecting group and the duration of the process, three main products in different ratios are formed. Along with the quinolin-2-ones, resulting from the classic Knorr cyclization, an indole derivative and a spirocyclic product have also been obtained from the COOEt-protected substrate. It has been demonstrated that the obtained indole derivative is capable of further dearomative spirocyclization under the studied conditions.